Problem-Based Learning (PBL) in Science Education: A Literature Review Study - Rizal, Saipul; Prayogi, Saiful; Muhali, Muhali; Kurnia, Nova (Lensa: Jurnal Kependidikan Fisika, 2023)
Problem-Based Learning (PBL) has emerged as a transformative pedagogical approach in science education, fostering student-centered learning through real-world problem-solving, critical thinking, and interdisciplinary inquiry. Unlike traditional lecture-based methods, PBL encourages active engagement, collaboration, and the application of scientific knowledge in meaningful contexts. Despite its benefits, challenges such as resource limitations, curriculum misalignment, inadequate teacher training, and ineffective assessment strategies hinder its widespread adoption. This study aims to conduct a comprehensive literature review on the implementation of PBL in science education, evaluating its impact on student learning, identifying key challenges, and exploring strategies to enhance its effectiveness. A systematic literature review methodology was employed, drawing from peer-reviewed journal articles, conference proceedings, and scholarly books published over the past two decades. Thematic analysis was used to categorize findings, focusing on areas such as student engagement, critical thinking, interdisciplinary learning, and instructional barriers. The review highlights that PBL significantly improves students’ comprehension and retention of scientific concepts while fostering scientific literacy and collaborative problem-solving skills. However, successful implementation requires institutional support, well-trained educators, and innovative assessment methods aligned with PBL’s inquiry-based nature. Key strategies for enhancing PBL include increased resource allocation, better curriculum integration, professional development for teachers, and the use of technology-driven tools to facilitate interactive learning. Future research should investigate long-term impacts of PBL, its adaptability in digital and hybrid learning environments, and its effectiveness across different STEM disciplines. By addressing these challenges and refining implementation strategies, PBL can continue to serve as a powerful approach for preparing students with the scientific competencies and problem-solving abilities needed in the 21st century. This study contributes to the growing body of knowledge on PBL and offers valuable insights for educators, policymakers, and researchers seeking to optimize science education through inquiry-driven, student-centered learning methodologies.